The "modest mask"? An investigation of vulnerable narcissists' implicit self-esteem. (1st December 2017) - Brown, Ashley A.; Brunell, Amy B.
Abstract: Vulnerable narcissists are entitled and self-absorbed, yet report low explicit self-esteem. We proposed a "Modest Mask Hypothesis, " predicting that vulnerable narcissism would be associated with low explicit self-esteem and high implicit self-esteem. We also sought to replicate previous work assessing grandiose narcissism and self-esteem. Studies 1 and 2 utilized two different versions of the self-esteem Implicit Association Test (IAT). Vulnerable narcissism did not appear to be associated with implicit self-esteem, whereas grandiose narcissism was explained by a combination of high implicit and high explicit self-esteem in Study 2. Study 3, utilizing a bogus pipeline methodology, revealed that vulnerable and grandiose narcissists believe the level of explicit self-esteem they report. Study 3 also revealed that under pressure to be honest, both grandiose and vulnerable narcissists report higher entitlement and exploitativeness, but only grandiose narcissists report higher grandiosity. Thus, mask models do not appear to explain narcissism.